Pengaruh Fasilitas Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT Transkom Integrasi Mandiri Tangerang Selatan - Bunga Safitri, Riyanti; Maharani, Haidilia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is motivated by the importance of work facilities and job satisfaction in improving employee performance at PT Transkom Integrasi Mandiri, where performance achievements over the past three years have not met the company’s target. The study aims to determine the influence of work facilities (X1) and job satisfaction (X2) on employee performance (Y), both partially and simultaneously. The research uses a quantitative approach with 65 respondents obtained through observation, interviews, and questionnaires, and the data were analyzed using multiple linear regression with SPSS 26. The results show that simultaneously X1 and X2 significantly affect Y, indicated by an F value of 85.986 > 2.750 and a significance of 0.000 < 0.05. Partially, work facilities have a positive and significant effect, with the regression equation Y = 7.513 + 0.814 X1, a correlation coefficient of 0.784, and an R square of 0.615, meaning 61.5% of performance is explained by work facilities while the remaining 38.5% is influenced by other factors. Job satisfaction also has a positive and significant effect through the equation Y = 5.543 + 0.911 X2, a correlation coefficient of 0.787, and an R square of 0.619, indicating that 61.9% of performance is explained by job satisfaction and the remaining 38.1% by other external factors. The study concludes that improving work facilities (X1) and job satisfaction directly (X2) contributes to enhancing employee performance, making both factors essential considerations in managerial decision-making.